Effects of consumption of contaminated feed with 2,4-dichlorophenoxyacetic acid (2,4-D) on the rat tibia: analysis by Raman spectroscopy and mechanical properties - Rocha, Déborah Ribeiro; Nery, Jaqueline Freire; Furini, Leonardo Negri [UNESP]; Constantino, Carlos José Leopoldo [UNESP]; Eller, Lizziane Kretli Winkelströter; Nai, Gisele Alborghetti; Nakagaki, Wilson Romero (Springer Nature, 2020)
Studies reported the harmful effects of 2,4-D on body tissues, provoking changes in the anatomy and physiology of the kidneys, liver, and testicles. Thus, the objective was to evaluate if there were alterations in the bone quality of the tibia of rats submitted to feed consumption that were exposed to three different 2,4-D doses. Male Wistar rats were divided into four groups: oral control group (C: feed consumption without 2,4-D contamination); low oral concentration group (G3: contaminated feed with low concentration of 2,4-D); medium concentration group (G6: contaminated feed with medium concentration of 2,4-D); and high concentration group (G9: contaminated feed with high concentration of 2,4-D). The results demonstrated alterations of the mechanical properties and Raman ratios of the tibias of the contaminated groups. The maximum load, maximum stress, elastic modulus, and the cortical area were lower in the G6 and G9 compared to C group. The mineral-to-matrix ratio (relative mineral to organic content) was lower in the G6 and G9 groups compared to C group, but carbonate-to-matrix ratio (indicator of bone turnover) was higher in both groups. Thus, it is possible to suggest that the 2,4-D herbicide performed deleterious effects on the bone quality of male Wistar rats.
Keywords: 2,4-D; Bone remodeling; Contamination; Herbicide; Tibias